Atividade experimental e o estudo da geração da vida em aulas de ciências: uma contribuição para essa discussão - Moreira, Maria Cristina do Amaral (2006)
This study aims at understanding students learning of a biological topic, namely how life is generated , when teaching is based on a sequence of laboratories activities carried out in the context of 7th year of primary school science lessons. To reach this goal, we planned a teaching intervention modeled on scientific inquiry: a sequence of laboratory activities was planned to provide students with data and empirical evidences so that they could develop their own arguments to explain the generation of life. The intervention was focused on understanding how does the fungus appear on tomatoes and also culture environment on Petri dishes. Throughout the process, students were asked to clarify their previous conceptions, formulate hypotheses, plan and carry out experiments in order to test their hypotheses and, finally, discuss and examine the results obtained. From the methodological point of view, the study made use of a set of data collecting instruments questionnaires, audio-recordings, and writing of texts by the students. Answers show that the teaching intervention not only promotes learning of the biological topic considered in this study but also provides understanding of the processes of scientific inquiry